Relations and Kleene Algebra in Computer Science 11th International Conference on Relational Methods in Computer Science, RelMiCS 2009, and 6th International Conference on Applications of Kleene Algebra, AKA 2009, Doha, Qatar, November 1-5, 2009, Proceedings - Berghammer, Rudolf; Jaoua, Ali; Möller, Bernhard (Theoretical Computer Science and General Issues, 2009)
The book constitutes the joint refereed proceedings of the 11th International Conference on Relational Methods in Computer Science, RelMiCS 2009, and the 6th International Conference on Applications of Kleene Algebras, AKA 2009, held in Doha, Qatar in November 2009. The 22 revised full papers presented together with 2 invited papers were carefully reviewed and selected from numerous submissions. The papers describe the calculus of relations and similar algebraic formalisms as methodological and conceptual tools with special focus on formal methods for software engineering, logics of programs and links to neighbouring disciplines. Their scope comprises relation relation algebras and Kleene algebras, related formalisms such as process algebras, fixed point calculi, idempotent semirings, quantales, allegories, dynamic algebras, cylindric algebras and their applications in areas such as verification, analysis and development of programs and algorithms relational formal methods such as B or Z, tabular methods, algebraic approaches to logics of programs, modal and dynamic logics, interval and temporal logics, algebraic semantics of programming languages , graph theory and combinatorial optimization, games, automata and language theory, mechanised and automated reasoning, decision procedures, spatio-temporal reasoning, knowledge acquisition, preference and scaling methods or information systems.